Possíveis impossibilidades - o objeto esculturado - Teixeira, Bruno da Silva (2013)
This research entitled "Possible Impossibilities - the object esculturado", proposes a reflection on my artistic activity, presenting the concepts, actions, intentions and strategies which are necessary to create this set of works that are structured from a sculptural activity that presents as final product, artistic pieces very similar to objects of common use and knowledge. These sculptures are constructed using the recovery and utilization of traditional techniques of sculpture associated with contemporary systems for obtaining three-dimensional shape. The molds of this artistic production are defined from the study of my activity as an artist active in the field of contemporary sculpture. The artistic proposition "Possible Impossibilities - the object esculturado" indicates an attitude and a commitment to articulate and reflective practice that aims to propose questions about the processes that make up the acts of seeing and understanding the objects around us.